Growth performance, carcass and meat quality of lambs supplemented with increasing levels of a tanniferous bush (Cistus ladanifer L.) and vegetable oils. - Francisco, A; Dentinho, M T; Alves, S P; Portugal, P V; Fernandes, F; Sengo, S; Jerónimo, E; Oliveira, M a; Costa, P; Sequeira, A; Bessa, R J B; Santos-Silva, J (Meat science, 2014)
The effects of dietary inclusion of Cistus ladanifer L. (CL) and a vegetable oil blend were evaluated on growth performance, carcass and meat quality of fifty four lambs that were assigned to 9 diets, corresponding to 3 levels of CL (50, 100 and 200 g/kg DM) and 3 levels of oil inclusion (0, 40 and 80 g/kg DM). Treatments had no effects on growth rate. Oil depressed dry matter intake (P = 0.017), carcass muscle (P = 0.041) and increased (P = 0.016) kidney knob channel fat. Chemical and physical meat quality traits were not affected by treatments. Off-flavour perception was higher for 8% of oil (P < 0.001). The level of 100 g/kg DM of CL inclusion improved meat stability after 7 days of storage. Supplementation with linseed and soybean oils (2:1) was a good approach to improve meat nutritional value from feedlot lambs, increasing total n-3 PUFA.
Keywords: carcass quality; Cistus ladanifer; lamb; meat quality; oil supplementation

Nutritional evaluation of the lipid fraction of Iberian red deer (Cervus elaphus hispanicus) tenderloin. - Quaresma, M a G; Trigo-Rodrigues, I; Alves, S P; Martins, S I V; Barreto, a S; Bessa, R J B (Meat science, 2012)
The meat lipid fraction of psoas major muscle from 20 adult (10 males and 10 females) feral Iberian red deer (Cervus elaphus hispanicus) was characterized by quantification of total fat, total cholesterol, vitamin E and fatty acid (FA) composition, including detailed trans octadecenoate isomers and conjugated linoleic acid (CLA) isomeric profile. The total lipid content revealed a very lean meat (0.99 g/100g of meat), with total cholesterol content averaging 55.6 mg/100g of muscle. The FA profile displayed a very high PUFA level for ruminant meat (30.2g/100g FA). The 18:2 cis-9,trans-11 content was fairly low (0.26% of total FA) compared with other ruminant meats. The comparison of stags and hinds showed more similarities than differences. Nevertheless, hinds displayed superior contents of α-tocopherol and trans MUFA and a better n-6/n-3 ratio than stags.
Keywords: cervus elaphus hispanicus; Cholesterol; CLA; Fatty acid profile; meat quality; Vitamin E